Laboratory Micro-X-Ray Fluorescence Spectroscopy Instrumentation and Applications - Haschke, Michael; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
Micro-X-ray fluorescence offers the possibility for a position- sensitive and non-destructive analysis that can be used for the analysis of non-homogeneous materials and layer systems. This analytical technique has shown a dynamic development in the last 15 years and is used for the analysis of small particles, inclusions, of elemental distributions for a wide range of different applications both in research and quality control. The first experiments were performed on synchrotrons but there is a requirement for laboratory instruments which offers a fast and immediate access for analytical results. The book discuss the main components of a µ-XRF instrument and the different measurement modes, it gives an overview about the various instruments types, considers the special requirements for quantification of non-homogeneous materials and presents a wide range of application for single point and multi-point analysis as well as for distribution analysis in one, two and three dimensions.
XRF-Basics -- Main Components of X-Ray Spectrometers -- Special Requirements for µ-XRF -- Quantification -- Sample Preparation -- Relations to Other Analytical Methods -- Applications.
Keywords: Spectroscopy; Microscopy; Materials—Surfaces.; Thin films; Physical measurements; Measurement .; Surfaces (Physics).; Interfaces (Physical sciences).; Spectroscopy and Microscopy; Surfaces and Interfaces, Thin Films; Measurement Science and Instrumentation; Spectroscopy/Spectrometry.; Surface and Interface Science, Thin Films